ASSESSING THE CONTRIBUTION OF THE THARI PROGRAMME IN PROTECTING CHILDREN AGAINST VIOLENCE AND ENHANCING SCHOOL SAFETY - Reyneke, Roelf (International Journal of Child, Youth and Family Studies, 2024)
This study examines the Thari pilot programme, developed by the Adopt-a-School Foundation as a potential solution to address school violence and children’s psychosocial health in South Africa. Employing an exploratory sequential mixed methods research design (QUAL-quan), the study evaluates the effectiveness of the Thari programme in providing essential psychosocial support services to children. The primary objective of the programme is to foster safe and violence-free learning environments that are academically effective, gender-sensitive, inclusive, and conducive to the health and well-being of all education stakeholders. The paper explores the psychosocial interventions employed by the Thari programme and assesses their contributions in creating secure and violence-free learning environments. The study findings offer support for the utilisation of psychosocial interventions in schools, as evidence suggests that these interventions positively impact school safety.